Exponential stability in a Timoshenko system of type III. Issue 17 (22nd November 2022) - Qin, Yuming; Li, Zhuang
Abstract : In this paper, a Timoshenko system with a delay term and a thermo-viscoelastic damping of type III subjected to Dirichlet–Dirichlet–Neumann boundary conditions will be considered. Exploiting energy method to produce a suitable Lyapunov functional, we establish the global existence and exponential decay of energy for Timoshenko system of type III.